Human Capital for Start-up Business Implementation over Home Care “4 Care” Application Programs - Wisnu Budi Prasetyo; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Penerbit Kemala Indonesia, 2019)
At present, business competition in the health care industry is getting tighter and encouraging companies to plan innovative HR fulfillment strategies. To capture market needs, companies must have added value to their human resources. In addition, PT Rembaka Catur Sekawan as a company that has the 4 Care brand must also have a good HR strategy to be able to compete with competitors. To compete and survive, the company's focus activities and business processes must concentrate on dynamic customer needs until the goals of meeting customer needs and customer satisfaction are met. Therefore, our initial business focused on how to educate about the importance of mobile-based health services so that customers are provided with ease in determining services without having to leave home or residence, but health workers are present before customers. To meet the dynamic needs of customers, a Human Capital Strategy is needed strong and capable and always follows the times